Apparent cooperativity and apparent hyperbolic behavior of enzyme mixtures acting on the same substrate. (1st November 2016) - Cappiello, Mario; Balestri, Francesco; Moschini, Roberta; Del-Corso, Antonella; Mura, Umberto
Abstract: It is well known that a negative cooperative behavior displayed by a monomeric enzyme may be associated with the simultaneous presence of two enzymes acting on the same substrate. In this paper, emphasis is given to the effect exerted by a rapid equilibrium between the enzyme forms in leading to a hyperbolic behavior, thus masking the presence of multiple enzyme forms.